Epidemiological Distribution of Human Immunodeficiency Virus (HIV) among Residents of Port Harcourt Metropolis in Rivers State Nigeria - Nwalozie, Rhoda; Kareem, Jubril Adeyinka; Ikpo, Precious Etinosa (Asian Journal of Research in Infectious Diseases, 2024)
Background: Human Immunodeficiency Virus is a lentivirus, a member of Retroviridae family that causes Acquired Immune Deficiency Syndrome. Globally, it was estimated that about 0.7% adult, aged 15- 49 years are living with HIV, with a prevalence of about 1.4% in Nigeria. However, a challenge lies in the insufficient and unreliable data present in much of the epidemiological research conducted in various countries and states. Therefore, this study aims to tackle this issue by focusing on gathering comprehensive demographic data and examining the distribution's impact of HIV among the subjects. Aim: To examine the Epidemiological Distribution of HIV among Residents of Port Harcourt Metropolis in Rivers State, Nigeria. Methodology: A cross-sectional study was conducted in the Port Harcourt metropolis, involving adult participants aged 20 years and above selected by simple randomized method among outpatients attending the Rivers State University Teaching Hospital, Port Harcourt. A total of 392 individuals provided consent and were recruited at the hospital. The study investigated variables such as age, gender, marital status, education level and occupation. Samples were collected and examined using the ELISA method under aseptic conditions. Statistical analysis was performed using SPSS version 28, including the calculation of Mann-Whitney U and Kruskal-Wallis test values. Results: The overall study revealed a prevalence of 1.02%, with only 4 individuals testing positive. Participants were grouped based on various demographics: age (P= .503), gender (P= .142), educational levels (P= .028), marital status (P= .000), and occupation (P= .733), with corresponding p-values indicating significance levels (P<0.05=Significant, P>0.05=Not Significant). Two demographic categories showed statistical significance: marital status, with higher prevalence among singles than married individuals, and educational level, with higher prevalence among those with no formal education. Conclusion: This study showed low HIV prevalence in Port Harcourt. Marital and educational demographics impacted infection distribution such that married, single, and formal education level increases HIV risk. Health education, community HIV testing, consistent monitoring, and regular data updates are strongly advised as crucial measures in the fight against HIV infection.